LITERATURE REVIEW : PENERAPAN LATIHAN KEMAMPUAN POSITIF TERHADAP PENINGKATAN HARGA DIRI RENDAH PADA KLIEN YANG MENGALAMI SKIZOFRENIA DENGAN GANGGUAN KONSEP DIRI HARGA DIRI RENDAH - Bayu Seto Rindi Atmojo, Mustika Ayu Purbaningrum (AKPER Pemkab Purworejo, 2021)
ABSTRACT Background : Positive ability is the ability or positive aspect of an individual to identify the ability that exists in the individual itself, so that clients can choose activities according to their abilities. In patients with low self-esteem, they see that they are not useful and feel they are not able to, by practicing positive abilities, they can explore aspects of their positive abilities so that they are expected to be able to see themselves useful and become good individuals. Objective: To determine the application of positive ability exercises in helping to overcome the problem of low self-esteem in patients with mental disorders. Method: The study used in this study was a literature review of positive ability exercises. Searching for the article is done by Google Scholar or Google Scholar, published from 2015 to 2020 which is accessed fulltext in PDF format. Of the 5 studies used 3 of them used the case study method, 1 the other used the Quasi Experimental Pre-post without control method and 1 the other used the lecture and discussion method. Results: Literature review shows that positive ability exercises vary greatly. The positive skills training consists of self-dressing activities, sewing therapy, washing activities, drawing activities and Plant Therapy activities. Significantly shows that all positive ability exercises can enhance and maintain the abilities that the client still has. Conclusion: Positive ability training can be used to overcome nursing problems in patients with schizophrenia with impaired self-concept of low self-esteem.